ChemInform Abstract: The Synthesis of Cyclophellitol‐Aziridine and its Configurational and Functional Isomers. Issue 41 (September 2016) - Jiang, Jianbing; Artola, Marta; Beenakker, Thomas J. M.; Schroeder, Sybrin P.; Petracca, Rita; de Boer, Casper; Aerts, Johannes M. F. G.; van der Marel, Gijsbert A.; Codee, Jeroen D. C.; Overkleeft, Herman S.
Abstract: Review: [45 refs.